Sealing ring and preparation method thereof
By micro-textured processing on the surface of the sealing ring and plated with the silicon transition layer and the silicon-doped diamond-like functional layer, the problem of oil leakage caused by wear and fatigue of the sealing ring is solved, and the effect of reducing friction coefficient and improving wear resistance and service life is achieved.
Patent Information
- Application Number
- CN202411681700.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-25
AI Technical Summary
The sealing ring is prone to oil leakage due to wear and fatigue during use, and the prior art is difficult to effectively solve this problem, especially in high friction environments.
By performing microtexture processing on the surface of the rubber ring matrix of the sealing ring, a microtexture region with pits is formed, and a silicon transition layer and a silicon-doped diamond-like functional layer are plated thereon, reducing the friction coefficient and improving wear resistance.
The friction coefficient of the sealing ring is significantly reduced, the adhesion hysteresis effect is reduced, the wear resistance and service life of the sealing ring is improved, and the combined strength and hardness are also improved.
Smart Images

Figure CN119508495A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sealing rings, and in particular relates to a micro-textured super-wear-resistant sealing ring and a preparation method thereof. Background Art
[0002] Sealing rings are essential and important basic components of hydraulic and transmission systems of construction machinery. The performance of sealing rings directly determines the performance, quality and reliability of construction machinery products. According to statistics, sealing failure is one of the main causes of failures in hydraulic and transmission systems. If the sealing fails and leaks oil during the three-guarantee period, it will lead to reduced operating efficiency of the main machine and environmental pollution, or even cause safety accidents, resulting in high after-sales costs and seriously affecting the market reputation of the product. The main causes of failure of sealing rings are aging, wear, fatigue, and installation errors, among which wear is the main factor causing oil leakage due to damage and failure of sealing rings. Due to the viscoelastic properties of rubber sealing ring materials, when the sealing ring contacts and moves with the metal counterpart, severe adhesion hysteresis will occur, resulting in extremely high friction, causing the sealing ring to be easily worn and fatigued.
[0003] At present, the methods to improve the performance of sealing rings include improving the base material, optimizing the sealing ring structure design and the sealing ring surface treatment. Commonly used sealing ring materials include organic polymers such as fluororubber and polytetrafluoroethylene. The friction and wear performance of the rubber matrix is improved by adding inorganic fillers (carbon fiber, graphene, SiO2, etc.) and resins (PF, PU) with wear resistance and self-lubricating functions. This is technically difficult and costly. In addition, the sealing ring structure needs to match the whole machine system. Changing the sealing ring structure design will affect the structure of the whole machine system, which is technically difficult and difficult to implement. Summary of the invention
[0004] In order to solve the deficiencies of the prior art, the present invention provides a micro-textured super wear-resistant sealing ring, which is dually constructed by micro-texture design and wear-resistant coating to reduce the friction coefficient, improve wear resistance, and extend the service life of the sealing ring, and has a high value for promotion and application.
[0005] The first aspect of the present invention provides a sealing ring, which is composed of a rubber ring substrate, a silicon transition layer and a silicon-doped diamond-like functional layer, wherein:
[0006] The entire or part of the surface of the rubber ring substrate is provided with a micro-textured area, wherein the micro-textured area contains pits.
[0007] The silicon transition layer is attached to the entire or partial surface of the rubber ring substrate, and the silicon transition layer covers the entire or partial micro-textured area, and
[0008] The silicon-doped diamond-like carbon functional layer is attached to the silicon transition layer.
[0009] In certain embodiments, the portion of the surface of the rubber ring substrate includes the surface of the rubber ring substrate in contact with an object (eg, a metal counterpart).
[0010] In some embodiments, the pits occupy 30% to 50% of the surface area of the micro-textured region, and the cross-sectional area of the pits is less than or equal to 1500 μm. 2 In some embodiments, the pits occupy 30%, 35%, 40%, 45%, 50% of the surface area of the micro-textured region. In some embodiments, the cross-sectional area of the pits is 50 μm 2 ~1500μm 2 .
[0011] In certain embodiments, the cross-section of the pit is circular, regular hexagonal, regular pentagonal, rhombus, square or equilateral triangle, the diameter of the circular cross-section is less than or equal to 30 μm, and the side length of the regular hexagonal, regular pentagonal, rhombus, square and equilateral triangle cross-section is less than or equal to 30 μm.
[0012] In some embodiments, the diameter of the circular cross section is 15-30 μm. In some embodiments, the diameter of the circular cross section is 15, 17, 20, 23, 25, 27, 30 μm.
[0013] In some embodiments, the side length of the cross section of the regular hexagon, regular pentagon, rhombus, square and equilateral triangle is 15 to 30 μm. In some embodiments, the side length of the cross section of the regular hexagon, regular pentagon, rhombus, square and equilateral triangle is 15, 17, 20, 23, 25, 27, 30 μm.
[0014] In some embodiments, the depth of the pit is 10-20 μm. In some embodiments, the depth of the pit is 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 μm.
[0015] In certain embodiments, the longitudinal cross-section of the recess is rectangular, square, trapezoidal, semicircular, triangular or irregular.
[0016] In certain embodiments, the pits are pillar-shaped pits.
[0017] In certain embodiments, the pits are uniformly distributed across the microtextured region.
[0018] In some embodiments, the total thickness of the silicon transition layer and the silicon-doped diamond-like functional layer is 200-300 nm. In some embodiments, the total thickness of the silicon transition layer and the silicon-doped diamond-like functional layer is 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300 nm.
[0019] In some embodiments, the thickness of the silicon transition layer is 50-100 nm. In some embodiments, the thickness of the silicon transition layer is 50, 60, 70, 80, 90, 100 nm.
[0020] In some embodiments, the thickness of the silicon-doped diamond-like functional layer is 150-200 nm. In some embodiments, the thickness of the silicon-doped diamond-like functional layer is 150, 160, 170, 180, 190, 200 nm.
[0021] In certain embodiments, the rubber ring substrate is selected from a fluororubber ring, a nitrile rubber ring, a polyurethane rubber ring, an EPDM rubber ring, and a silicone rubber ring.
[0022] The second aspect of the present invention provides a method for preparing the sealing ring according to the first aspect of the present invention, comprising:
[0023] (1) micro-texturing the rubber ring substrate to form a micro-textured region on the entire or partial surface of the rubber ring substrate, wherein the micro-textured region contains pits;
[0024] (2) Cleaning;
[0025] (3) Coating, wherein the coating includes a silicon-coated transition layer and a silicon-doped diamond-like functional layer in sequence.
[0026] In certain embodiments, the rubber ring substrate is selected from a fluororubber ring, a nitrile rubber ring, a polyurethane rubber ring, an EPDM rubber ring, and a silicone rubber ring.
[0027] In certain embodiments, step (1) further includes pre-cleaning to remove stains on the surface of the rubber ring substrate.
[0028] In certain embodiments, the pre-cleaning comprises:
[0029] Place the rubber ring substrate into the cleaning agent for cleaning.
[0030] Wash in water,
[0031] drying.
[0032] In certain embodiments, the pre-cleaning comprises placing the rubber ring substrate in a cleaning solvent for ultrasonic cleaning.
[0033] In certain embodiments, the pre-cleaning comprises ultrasonic cleaning in water.
[0034] In certain embodiments, the cleaning reagent is selected from an alkaline cleaning reagent, an acidic cleaning reagent, and a neutral cleaning reagent.
[0035] In some embodiments, the cleaning agent is selected from an organic solvent. In some embodiments, the cleaning agent is selected from anhydrous ethanol and acetone.
[0036] In certain embodiments, step (1) comprises:
[0037] 1.1) Using glass or silicon wafer as substrate to make photolithography mask;
[0038] 1.2) coating the rubber ring substrate with photoresist, and processing the photoresist using a photolithography machine according to a photolithography mask;
[0039] 1.3) placing the workpiece processed in step 1.2) in a reactive ion etcher for ion etching.
[0040] In some embodiments, the etching time is 12-17 min. In some embodiments, the etching time is 13-15 min.
[0041] In certain embodiments, in step (1), a photolithography mask is prepared according to the cross-sectional shape of the pit, wherein the cross-sectional shape of the pit is circular, regular hexagonal, regular pentagonal, rhombus, square or equilateral triangle, the diameter of the circular cross-sectional shape is 15 to 30 μm, and the side length of the cross-sectional shape of the regular hexagonal, regular pentagonal, rhombus, square and equilateral triangle is 15 to 30 μm.
[0042] In some embodiments, the diameter of the circular cross section is 15-30 μm. In some embodiments, the diameter of the circular cross section is 15, 17, 20, 23, 25, 27, 30 μm.
[0043] In some embodiments, the side length of the cross section of the regular hexagon, regular pentagon, rhombus, square and equilateral triangle is 15 to 30 μm. In some embodiments, the side length of the cross section of the regular hexagon, regular pentagon, rhombus, square and equilateral triangle is 15, 17, 20, 23, 25, 27, 30 μm.
[0044] In certain embodiments, the cross-sectional shapes of the pits are uniformly distributed on the surface of the photolithography mask.
[0045] In some embodiments, the cross-sectional shape of the pit accounts for 30%-50% of the surface area of the photolithography mask. In some embodiments, the cross-sectional shape of the pit accounts for 30%, 35%, 40%, 45%, 50% of the surface area of the photolithography mask.
[0046] In certain embodiments, in step (1), a photolithography mask is produced by laser direct writing.
[0047] In certain embodiments, in step (1), the photoresist is uniformly coated by spin coating.
[0048] In certain embodiments, in step (1), the photoresist is a positive photoresist.
[0049] In certain embodiments, in step (1), the etching gas for ion etching is tetrafluoromethane, the gas flow rate is 50-100 sccm, the radio frequency power is 80-100 W, and the working pressure is a negative pressure of 1.3-2.6 Pa.
[0050] In certain embodiments, in step (1), the gas flow rate of the ion etching is 60-80 sccm.
[0051] In certain embodiments, in step (1), the radio frequency power of the ion etching is 80-90W.
[0052] In certain embodiments, in step (1), the working pressure of the ion etching is a negative pressure of 1.8 to 2.1 Pa.
[0053] In certain embodiments, step (2) comprises:
[0054] 2.1) Clean and remove stains on the surface of the rubber ring substrate;
[0055] 2.2) Cleaning the workpiece obtained in step 2.1) with plasma gas in a vacuum chamber.
[0056] In certain embodiments, the plasma gas is selected from argon and nitrogen.
[0057] In certain embodiments, in step 2.1), the cleaning is as described in the pre-cleaning of the present invention.
[0058] In certain embodiments, the step 2.2) comprises:
[0059] 2.2.1) Place the workpiece obtained in step 2.1) into the vacuum chamber, adjust the rotating speed to 1.5-3 r / min, and draw the vacuum pressure to (1-2)×10 -2 Pa;
[0060] 2.2.2) Plasma gas is introduced, the flow rate of the plasma gas is 10-15 sccm, and the vacuum pressure is adjusted to (1.5-3)×10 -2 Pa;
[0061] 2.2.3) Turn on the Hall ion source, set the voltage to 700-900 V, and the duration to 8-20 min.
[0062] In certain embodiments, in step 2.2.1), the rotating speed of the rotating rack is 1.8 r / min.
[0063] In certain embodiments, in step 2.2.1), the vacuum pressure is 1.5×10 -2 Pa.
[0064] In certain embodiments, in step 2.2.2), the flow rate of the plasma gas is 12-13 sccm.
[0065] In certain embodiments, in step 2.2.2), the vacuum pressure is (1.8-2.5)×10 -2 Pa.
[0066] In certain embodiments, in step 2.2.3), the voltage is 700-820V.
[0067] In certain embodiments, in step 2.2.3), the duration is 10 to 15 min. In certain embodiments, the duration is 10 to 12 min.
[0068] In certain embodiments, step (3) comprises:
[0069] 3.1) Turn on the magnetron sputtering cathode to deposit a silicon transition layer, wherein the target material of the magnetron sputtering cathode is silicon, the power is 1.2-1.5 kW, the voltage is 15-30 V, the current is 10-25 A, and the deposition time is 20-25 min;
[0070] 3.2) Turn on the pulse arc ion source and magnetron sputtering cathode, and adjust the vacuum pressure to (1-2)×10 -2 Pa, silicon-doped diamond-like functional layer deposition is carried out, the target material of the pulse arc ion source is high-purity graphite, the working voltage is 250-300V, the working frequency is 3-10Hz, the number of pulses is 6000-8000 times, the target material of the electromagnetic controlled sputtering cathode is silicon, the power is 0.2-0.5kw, the voltage is 15-30V, and the current is 10-25A.
[0071] In certain embodiments, in step 3.1), the magnetron sputtering cathode power is 1.2-1.3 kW.
[0072] In certain embodiments, in step 3.1), the electromagnetic controlled sputtering cathode voltage is 20-25V.
[0073] In certain embodiments, in step 3.1), the cathode current of the electromagnetic sputtering is 15-20A.
[0074] In certain embodiments, in step 3.1), the deposition time is 22 to 25 minutes.
[0075] In certain embodiments, in step 3.2), the vacuum pressure is (1.5-1.8)×10 -2 Pa.
[0076] In certain embodiments, in step 3.2), the pulse arc ion source has an operating voltage of 250-280V.
[0077] In certain embodiments, in step 3.2), the pulse arc ion source operates at a frequency of 5 to 7 Hz.
[0078] In certain embodiments, in step 3.2), the pulse number of the pulse arc ion source is 6000 to 8000 times.
[0079] In certain embodiments, in step 3.2), the electromagnetic controlled sputtering cathode power is 0.3-0.5 kw.
[0080] In certain embodiments, in step 3.2), the electromagnetic controlled sputtering cathode voltage is 20-25V.
[0081] In certain embodiments, in step 3.2), the cathode current of the electromagnetic sputtering is 15-20A.
[0082] The third aspect of the present invention provides the sealing ring described in the first aspect of the present invention for sealing an oil cylinder.
[0083] In certain embodiments, the seal is used to seal a crane cylinder.
[0084] Definition of terms
[0085] In this application, unless otherwise specified, the scientific and technical terms used herein have the meanings commonly understood by those skilled in the art. Meanwhile, in order to better understand the present invention, the definitions and explanations of the relevant terms are provided below.
[0086] When the terms "for example," "such as," or variations thereof are used herein, these terms will not be considered as limiting terms, but will be interpreted to mean "including, but not limited to," "not limited to."
[0087] When the terms "comprising," "including," or variations thereof are used herein, the terms "consisting of," and "consisting essentially of" are also provided with a meaning.
[0088] The terms "a," "an," and "the" and similar referents in the context of describing the invention (especially in the context of the following claims) should be construed to cover both the singular and the plural, unless otherwise indicated herein or clearly contradicted by context.
[0089] In this application, the term "microtexture" refers to a microstructure with a specific shape, arrangement and size processed on the surface of a material. Microtexture originated from bionics, which applies the excellent properties of the morphology and structure of natural organisms to science and technology.
[0090] In this application, the term "photolithography mask", also known as "mask", "photolithography mask", refers to a graphic master used in the photolithography process, which is usually used to produce a designed graphic on a film, plastic or glass substrate material.
[0091] In this application, the term "photoresist", also known as "photoresist", refers to an etch-resistant film material whose solubility changes when exposed to ultraviolet light, electron beam, ion beam, X-ray, etc. Photoresist can be divided into positive photoresist and negative photoresist. Positive photoresist means that the exposed part is soluble in the developer, while the unexposed part is insoluble in the developer. After development, the photoresist pattern remaining on the substrate is the same as the target pattern on the mask. The pattern of negative photoresist after development is opposite to the pattern on the mask.
[0092] In the present application, the term "vacuum pressure" refers to the absolute value of the difference between the absolute pressure in the reaction chamber and the standard atmospheric pressure when the absolute pressure in the reaction chamber is lower than the standard atmospheric pressure.
[0093] In the present application, the term "negative pressure" refers to a gas pressure state lower than the standard atmospheric pressure, and refers to the difference from the standard atmospheric pressure. For example, a negative pressure of 1.3 Pa means 1.3 Pa lower than the standard atmospheric pressure.
[0094] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0095] Beneficial effects achieved by the present invention:
[0096] (1) The sealing ring of the present invention has a small friction coefficient, and is not prone to adhesion hysteresis when in contact with a metal counterpart. The surface of the sealing ring of the present invention is provided with a micro-texture, which can store hydraulic oil. When the micro-texture contains hydraulic oil, a micro-fluid pressure effect can be generated, further reducing friction resistance and improving lubrication conditions. The sealing ring of the present invention has a high bonding strength, and the attached silicon transition layer and silicon-doped diamond-like functional layer are not easy to peel off from the rubber ring matrix. According to the ASTM D3359-08 standard, the bonding strength can reach 5A grade. The sealing ring of the present invention has a high hardness, and the hardness value can reach 4200HV, so that the sealing ring can be used in a high-load environment. The sealing ring of the present invention has good wear resistance, good quality, and a long service life, and has a high value for promotion and application.
[0097] (2) The present invention designs micro-textures based on natural animals, such as the pits designed based on sand lizards and pythons with regular hexagonal and circular cross-sections. These pit bionic micro-textures produce a roughening effect on the surface of the sealing ring, that is, a fine and uniform microscopic concave-convex structure is formed on the surface. When in contact with other objects and in relative motion, a microscopic "rolling" interface is formed, allowing the object to pass relatively smoothly, thereby reducing friction and improving the wear resistance of the sealing ring. In addition, the bionic micro-texture affects the growth of the film layer during the coating process, making the formed film layer denser and more uniform, thereby improving the hardness. In addition, the bionic micro-texture can improve the adhesion of the film layer during subsequent coating, and enhance the mechanical bonding force between the film layer and the substrate. In particular, when the sealing ring is subjected to external forces, such as heavy loads and impacts, the film layer is not easy to fall off and peel off from the substrate, thereby improving the quality of the surface film layer. Furthermore, the inventors found that when the pits occupy 30% to 50% of the surface area of the micro-texture region, the sealing ring can have the best performance and the smallest friction coefficient. The inventors analyzed that the micro-texture with appropriate density forms a network structure distributed vertically and horizontally to provide support. When the pit density is too small, the effect is not obvious, and when the density is too large, it will damage the rubber ring matrix.
[0098] (3) The sealing ring of the present invention is plated with a composite structure of a silicon transition layer and a silicon-doped diamond-like functional layer on the surface of the rubber ring substrate. A schematic diagram of the surface coating of the sealing ring of one embodiment of the present invention is shown in FIG. Figure 2 As shown, the composite structure has strong hardness and high wear resistance on the basis of ensuring the bonding force between the coating and the substrate. The inventors found that the chemical properties of silicon and the rubber ring substrate material are relatively similar, and the bonding force between the two is relatively strong. The use of a silicon transition layer can alleviate the difference in material mechanical properties between the surface functional layer and the rubber ring substrate material, improve the bonding force of the functional layer, and make the coating less likely to peel off from the rubber substrate. The inventors also found that doping silicon in the diamond-like coating can improve the performance of the functional layer, and the dispersion strengthening effect of the nanoparticle SiC phase can play a role in wear resistance and friction reduction.
[0099] (4) The method for preparing a sealing ring of the present invention is simple and easy to operate, and by selecting appropriate process conditions and parameters, the prepared sealing ring has the aforementioned beneficial effects. In particular, the present invention uses ion etching for micro-texturing processing, avoiding the defects of conventional micro-texturing processing using lasers. Laser processing is a thermal processing, and the large amount of heat generated will cause a heat-affected zone to appear on the rubber surface, forming cracks, a melt layer, etc., destroying the rubber material, while the ion etching technology can avoid the heat effect. In addition, the present invention sets the ion etching time to control the depth of the micro-texture pits, and adjusts the coating film thickness by controlling the number of pulses, so that the performance of the obtained sealing ring is optimized. BRIEF DESCRIPTION OF THE DRAWINGS
[0100] Figure 1 Schematic diagram of the bionic micro-texture region of certain embodiments of the present invention, wherein: 1 - regular hexagonal cross section; 2 - circular cross section.
[0101] Figure 2 Schematic diagram of the surface coating of a sealing ring according to an embodiment of the present invention.
[0102] Figure 3 It is the criterion for judging the bonding strength. DETAILED DESCRIPTION
[0103] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0104] 1. Performance testing method
[0105] 1. Hardness
[0106] The hardness of the coated samples was tested using a Vickers hardness tester (Laizhou Huayin HV-50). 3 to 5 flat points without obvious defects were tested on the surface of the test sample, and the average value was taken. The hardness tester load was set to 0.3N-0.5N, and the holding time was 10s-15s.
[0107] 2. Bonding strength
[0108] According to ASTM D3359-08 standard, the X-cutting method is used to test the bonding strength of the sealing ring film of the present invention. First, the sample surface film is cut into an X shape with a blade, and the angle of the cross line is 30° to 45°. Under a constant pressure of 10N, a 3M tape (adhesion force of 47N / 100mm) is adhered to the film surface. After 2 minutes, the tape is torn off along 180°. The cracks and peeling degree of the surface film in the X-cut area and the adhesion of the tape surface are observed. Figure 3 The bonding strength judgment criteria shown are used to evaluate the adhesion of the film.
[0109] 3. Friction coefficient
[0110] The friction coefficient of the seal ring after coating was tested using a friction and wear tester (UMT friction and wear tester TriboLab). The test conditions are as follows: test pressure 30N, room temperature, speed 50r / min, time 15min, and the roughness of the grinding pair Ra2.0.
[0111] 2. Embodiment
[0112] Example 1
[0113] (1) Pretreatment: Place the fluororubber seal ring (hardness: about 100 HV; friction coefficient: about 0.8) in anhydrous ethanol and perform ultrasonic cleaning for 10 minutes to remove oil, dust and impurities on the surface of the part. Then immerse it in pure water and perform ultrasonic cleaning for 10 minutes to remove the anhydrous ethanol residue on the surface of the part. After cleaning, place the part in a 50°C drying oven for 30 minutes.
[0114] (2) Microtexture processing: Using glass as the substrate, laser direct writing is used to process circular structures designed based on python scales (such as Figure 1 The bionic structure of the circular cross section 2 is shown in the figure, and a photolithography mask is made. A layer of positive photoresist is evenly coated on the cleaned sealing ring by spin coating, and the bionic pattern on the photolithography mask is transferred to the photoresist by a photolithography machine. The sealing ring is placed in a reactive ion etcher for micro-texturing processing. The etching gas is tetrafluoromethane (CF4), the gas flow is 60sccm, the radio frequency power is 90W, the working pressure is a negative pressure of 2.1Pa, and the etching time is 13min. Evenly distributed columnar pits are formed in the micro-texturing processing area on the surface of the sealing ring. The pits account for 40% of the surface area of the micro-texture area, the pit depth is 15μm, the bottom surface of the pit is circular, and the diameter of each circular bottom surface is 20μm. After etching, repeat step (1).
[0115] (3) Cleaning of the sealing ring before coating: Place the treated sealing ring into the vacuum chamber, adjust the rotating speed to 1.8 r / min, and draw the vacuum pressure to 1.5×10 -2 Pa, Ar was introduced with an Ar flow rate of 12 sccm, and the vacuum pressure was adjusted to 1.8×10 -2 Pa, turn on the Hall ion source, set the voltage to 820 V, and the duration to 12 min.
[0116] (4) Sealing ring coating: Turn on the magnetron sputtering cathode, excite the Si target, set the power to 1.2 kW, the voltage to 25 V, and the current to 20 A, and perform thin film deposition for 22 min to obtain a Si transition layer with a thickness of 70 nm, covering the micro-textured area. Then turn on the pulsed arc ion source and the magnetron sputtering cathode. The target material of the pulsed carbon ion source is high-purity graphite, and the target material of the magnetron sputtering cathode is Si. The vacuum pressure is 1.5×10 -2 Pa, set the pulse arc source working voltage to 280V, the working frequency to 7Hz, the number of pulses to 8000 times, set the power of the magnetron sputtering cathode to 0.5kw, the voltage to 25V, and the current to 20A, and obtain a Si-doped diamond-like functional layer with a thickness of 180nm, attached to the Si transition layer. After the vacuum chamber is cooled to room temperature, the sealing ring is taken out. Performance testing is performed, the fluororubber sealing ring is micro-textured, and after plating the Si silicon transition layer and the Si-doped diamond-like functional layer, the hardness value of the sealing ring reaches 4200HV, the bonding strength reaches 5A level, and the film layer dry friction coefficient is 0.11, which significantly improves the hardness and reduces the friction coefficient. The sealing ring sample prepared according to Example 1 is named A.
[0117] Example 2
[0118] (1) Pretreatment: Place the nitrile rubber sealing ring (hardness: about 40HV; friction coefficient: about 1.0) in anhydrous ethanol and perform ultrasonic vibration cleaning for 10 minutes to remove oil, dust and impurities on the surface of the part. Then immerse it in pure water and perform ultrasonic vibration for 10 minutes to remove the anhydrous ethanol residue on the surface of the part. After cleaning, place the part in a 50℃ drying oven for 30 minutes.
[0119] (2) Microtexture processing: Using glass as the substrate, laser direct writing is used to process regular hexagons (such as Figure 1 A bionic structure (shown in the cross section of the regular hexagon 1) is prepared to make a photolithography mask. A layer of positive photoresist is evenly coated on the cleaned sealing ring by spin coating, and the bionic pattern on the photolithography mask is transferred to the photoresist by a photolithography machine. The sealing ring is placed in a reactive ion etcher for micro-texturing processing. The etching gas is tetrafluoromethane (CF4), the gas flow is 80sccm, the radio frequency power is 80W, the working pressure is a negative pressure of 1.8Pa, and the etching time is 15min. Evenly distributed columnar pits are formed in the micro-texturing processing area on the surface of the sealing ring. The pits account for 40% of the surface area of the micro-texture area, the pit depth is 20μm, the bottom surface of the pit is a regular hexagon, and the side length of the bottom surface of each regular hexagon is 30μm. After etching, repeat step (1).
[0120] (3) Cleaning of the sealing ring before coating: Place the treated sealing ring into the vacuum chamber, adjust the rotating speed to 1.8 r / min, and draw the vacuum pressure to 1.5×10-2 Pa, Ar was introduced with an Ar flow rate of 13 sccm, and the vacuum pressure was adjusted to 2.5×10 -2 Pa, turn on the Hall ion source, set the voltage to 700 V, and hold for 10 min.
[0121] (4) Sealing ring coating: Turn on the magnetron sputtering cathode, excite the Si target, set the power to 1.3 kW, the cathode voltage to 20 V, and the current to 15 A, and perform 25 min of thin film deposition to obtain a Si transition layer with a thickness of 100 nm, covering the micro-textured area. Then turn on the pulsed arc ion source and the magnetron sputtering cathode. The target material of the pulsed carbon ion source is high-purity graphite, and the target material of the magnetron sputtering cathode is Si. The vacuum pressure is 1.8×10 -2 Pa, set pulse arc source operating voltage 250V, operating frequency 5Hz, pulse number 6000 times, set the power of magnetron sputtering cathode to 0.3kw, voltage is 20V, current is 15A, obtain Si doped diamond-like functional layer, thickness is 150nm, attached to Si transition layer.After vacuum chamber is cooled to room temperature, seal ring is taken out.Perform performance detection, micro-texture processing is carried out to nitrile rubber seal ring, and after plating Si silicon transition layer and Si doped diamond-like functional layer, the hardness value of seal ring reaches 3500HV, and bonding strength reaches 5A level, and film dry friction coefficient is 0.25, which significantly improves hardness and reduces friction coefficient.The seal ring sample prepared according to Example 2 is named B.
[0122] 3. Comparison
[0123] Comparative Example 1
[0124] The difference between Comparative Example 1 and Example 2 is that the bionic microtexture processing in step (2) is removed, and the pretreatment, pre-coating cleaning and coating processes are exactly the same. The sealing ring prepared according to Comparative Example 1 is tested for performance, and the hardness value is 2900 HV, the bonding strength reaches 5A level, and the dry friction coefficient of the film layer is 0.42.
[0125] It can be analyzed from the results that the surface bionic micro-texture design can reduce the friction coefficient and increase the hardness, which plays an important role in extending the service life of the sealing ring.
[0126] Comparative Examples 2 to 6
[0127] The difference between Comparative Examples 2 to 6 and Example 1 is only that the pulse number in step (4) of coating the sealing ring is different. The pulse number of each comparative example is shown in Table 1. The other process operations and parameters are completely the same. The sealing ring samples prepared according to Comparative Examples 2-6 are named CG in turn, among which Comparative Example 6 is not coated.
[0128] Table 1
[0129] serial number Sample name Pulse times Friction coefficient hardness Bonding strength Example 1 A 8000 0.11 4200HV 5A Comparative Example 2 C 7000 0.28 4160HV 5A Comparative Example 3 D 6000 0.39 3900HV 4A Comparative Example 4 E 5000 0.47 2500HV 4A Comparative Example 5 F 4000 0.48 1600HV 3A Comparative Example 6 G / 0.8 100HV /
[0130] The friction coefficient, hardness and bonding strength of the sealing ring AF are shown in Table 1. When the pulse number is 8000 times, the fluororubber sealing ring has the lowest friction coefficient and the highest hardness, and the bonding strength reaches 5A level. The wear resistance is significantly improved. It is speculated that the pulse number affects the film thickness, which in turn affects the wear resistance of the sealing ring.
[0131] Comparative Examples 7-9
[0132] The difference between Comparative Examples 7 to 9 and Example 2 is only the different etching times in step (2) microtexturing. The etching times of the comparative examples are shown in Table 2. The other process operations and parameters are completely the same. The sealing ring samples prepared according to Comparative Examples 7 to 9 are named HJ in turn.
[0133] Table 2
[0134]
[0135]
[0136] The friction coefficient, hardness and bonding strength of the sealing rings B and HJ are shown in Table 2. When the etching time is 15 min, the performance parameters of the nitrile rubber sealing ring achieve better results. It is speculated that the etching time affects the processing effect of the bionic microtexture, such as the depth of the pit. When the etching time is too short, the microtexture processing effect is not good, and when the etching time is too long, it affects the matrix structure.
[0137] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.
Claims
1. A sealing ring, which is composed of a rubber ring matrix, a silicon transition layer and a silicon-doped diamond-like functional layer, wherein: The entire or part of the surface of the rubber ring substrate is provided with a micro-textured area, wherein the micro-textured area contains pits. The silicon transition layer is attached to the entire or partial surface of the rubber ring substrate, and the silicon transition layer covers the entire or partial micro-textured area, and The silicon-doped diamond-like carbon functional layer is attached to the silicon transition layer.
2. The sealing ring according to claim 1, wherein: The pits account for 30% to 50% of the surface area of the micro-texture region, and the cross-sectional area of the pits is less than or equal to 1500 μm 2 , preferably 50 μm 2 ~1500μm 2 .
3. The sealing ring according to claim 1 or 2, wherein: The cross-section of the pit is circular, regular hexagon, regular pentagon, rhombus, square or equilateral triangle, the diameter of the circular cross-section is less than or equal to 30 μm, preferably 15 to 30 μm, and the side length of the regular hexagon, regular pentagon, rhombus, square and equilateral triangle cross-section is less than or equal to 30 μm, preferably 15 to 30 μm.
4. The sealing ring according to any one of claims 1 to 3, wherein: The depth of the pit is 10 to 20 μm.
5. The sealing ring according to any one of claims 1 to 4, wherein: The pits are evenly distributed in the micro-textured area.
6. The sealing ring according to any one of claims 1 to 5, wherein: The total thickness of the silicon transition layer and the silicon-doped diamond-like functional layer is 200-300 nm.
7. The sealing ring according to any one of claims 1 to 6, wherein: The thickness of the silicon transition layer is 50-100 nm.
8. The sealing ring according to any one of claims 1 to 7, wherein: The thickness of the silicon-doped diamond-like carbon functional layer is 150-200 nm.
9. The sealing ring according to any one of claims 1 to 8, wherein: The rubber ring matrix is selected from a fluororubber ring, a nitrile rubber ring, a polyurethane rubber ring, an EPDM rubber ring and a silicone rubber ring.
10. A method for preparing the sealing ring according to any one of claims 1 to 9, comprising: (1) micro-texturing the rubber ring substrate to form a micro-textured region on the entire or partial surface of the rubber ring substrate, wherein the micro-textured region contains pits; (2) Cleaning; (3) Coating, wherein the coating includes a silicon-coated transition layer and a silicon-doped diamond-like functional layer in sequence.
11. The method of claim 10, wherein: The rubber ring matrix is selected from a fluororubber ring, a nitrile rubber ring, a polyurethane rubber ring, an EPDM rubber ring and a silicone rubber ring.
12. The method according to claim 10 or 11, wherein Before step (1), pre-cleaning is also included to remove stains on the surface of the rubber ring substrate.
13. The method of claim 12, wherein: The pre-cleaning comprises: Place the rubber ring substrate into the cleaning agent for cleaning. Wash in water, drying; Preferably, the cleaning agent is selected from an alkaline cleaning agent, an acidic cleaning agent and a neutral cleaning agent; Preferably, the cleaning agent is selected from organic solvents, such as anhydrous ethanol and acetone.
14. The method according to any one of claims 10 to 13, wherein The step (1) comprises: 1.1) Using glass or silicon wafer as substrate to make photolithography mask; 1.2) coating the rubber ring substrate with photoresist, and processing the photoresist using a photolithography machine according to a photolithography mask; 1.3) placing the workpiece processed in step 1.2) in a reactive ion etcher for ion etching; Preferably, the etching time is 12-17 minutes.
15. The method according to any one of claims 10 to 14, wherein The step (1) includes one or more of the following features: - manufacturing a photolithography mask according to the cross-sectional shape of the pit, wherein the cross-sectional shape of the pit is circular, regular hexagonal, regular pentagonal, rhombus, square or equilateral triangle, the diameter of the circular cross-sectional shape is 15 to 30 μm, and the side length of the cross-sectional shape of the regular hexagonal, regular pentagonal, rhombus, square and equilateral triangle is 15 to 30 μm; - the cross-sectional shape of the pits is uniformly distributed on the surface of the photolithography mask; - the cross-sectional shape of the pit occupies 30%-50% of the surface area of the photolithography mask; -Making photolithography masks using laser direct writing; -Use spin coating to evenly coat the photoresist; - the photoresist is a positive photoresist; - The etching gas for the ion etching is tetrafluoromethane, the gas flow rate is 50-100 sccm, the radio frequency power is 80-100 W, and the working pressure is a negative pressure of 1.3-2.6 Pa.
16. The method according to any one of claims 10 to 15, wherein The step (2) comprises: 2.1) Cleaning and removing stains on the surface of the rubber ring substrate, preferably the cleaning is as described in claim 13; 2.2) Cleaning the workpiece obtained in step 2.1) with plasma gas in a vacuum chamber; Preferably, the plasma gas is selected from argon and nitrogen.
17. The method according to any one of claims 10 to 16, wherein: The step 2.2) comprises: 2.2.1) Place the workpiece obtained in step 2.1) into the vacuum chamber, adjust the rotating speed to 1.5-3 r / min, and draw the vacuum pressure to (1-2)×10 -2 Pa; 2.2.2) Plasma gas is introduced, the flow rate of the plasma gas is 10-15 sccm, and the vacuum pressure is adjusted to (1.5-3)×10 -2 Pa; 2.2.3) Turn on the Hall ion source, set the voltage to 700-900 V, and the duration to 8-20 min.
18. The method according to any one of claims 10 to 17, wherein The step (3) comprises: 3.1) Turn on the magnetron sputtering cathode to deposit a silicon transition layer, wherein the target material of the magnetron sputtering cathode is silicon, the power is 1.2-1.5 kW, the voltage is 15-30 V, the current is 10-25 A, and the deposition time is 20-25 min; 3.2) Turn on the pulse arc ion source and magnetron sputtering cathode, and adjust the vacuum pressure to (1-2)×10 -2 Pa, silicon-doped diamond-like functional layer deposition is carried out, the target material of the pulse arc ion source is high-purity graphite, the working voltage is 250-300V, the working frequency is 3-10Hz, the number of pulses is 6000-8000 times, the target material of the electromagnetic controlled sputtering cathode is silicon, the power is 0.2-0.5kw, the voltage is 15-30V, and the current is 10-25A.
19. The sealing ring according to any one of claims 1 to 9, which is used for sealing an oil cylinder, preferably for sealing a crane oil cylinder.
Citation Information
Cited By
Cutter-chip interface nanofluid infiltration method based on electroosmosis effect
CN116852167A